â€œDAMPING-OFFâ€ EM SEMENTEIRAS DE ð˜ˆð˜®ð˜¢ð˜³ð˜¢ð˜¯ð˜µð˜©ð˜¶ð˜´ spp. CAUSADO POR ð˜—ð˜ºð˜µð˜©ð˜ªð˜¶ð˜® sp. - Bialoskorski Neto, S.; Kimati, H. (REVISTA DE AGRICULTURA, 2020)
â€œDAMPING-OFFâ€ EM SEMENTEIRAS DE ð˜ˆð˜®ð˜¢ð˜³ð˜¢ð˜¯ð˜µð˜©ð˜¶ð˜´ spp. CAUSADO POR ð˜—ð˜ºð˜µð˜©ð˜ªð˜¶ð˜® sp.